Processos termoquímicos de resíduos agrícolas maranhenses: simulação usando aspen plus ® - MARTINS, Thaís Serra (2021)
The search for alternative sources that make the energy matrix more diversified and renewable has grown over the years, both in Brazil and in the world, which is why the interest in the use of biomass for energy purposes has increased. The products obtained from the processing of biomass, which may have energy potential, depend on the characteristics of this raw material and also on the processing technology. Therefore, there are several conversion methods that can be used, such as biochemical ones, which include anaerobic digestion and alcohol fermentation, and thermochemical conversion, which includes combustion, pyrolysis and gasification, among others. In the State of Maranhão, biomass from agricultural residues is very abundant, especially the babassu coconut husk and the açaí kernel, whose production in 2017 was above 50 and 18 thousand tons, respectively. The main uses of these residues are for the extraction of babassu seeds for the production of oil and for the production of açaí pulp. In this context, this study aimed to evaluate the products generated by the thermochemical processing of biomass, specifically by gasification, using babassu coconut and açaí as raw material, aiming at the production of energy and by-products of high added value. The study was carried out through computer simulation in the Aspen Plus software version 8.8 and the chemical compositions of each biomass were adapted to the model adopted, Model for Moving Coal Gasifier. Initially, a bibliographic survey of the elementary compositions of the studied biomasses was carried out in order to verify if there was any energetic potential of these fuels. Subsequently, the gasification process was simulated, finding significant yields of synthesis gas, 64.23% and 60.81% for the babassu coconut shell and açaí kernel, respectively, for both biomasses.